2019
DOI: 10.1093/dote/doz031
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic magnetic sphincter augmentation versus fundoplication for gastroesophageal reflux disease: systematic review and pooled analysis

Abstract: SUMMARY Magnetic sphincter augmentation (MSA) has been proposed as a less invasive, more appealing alternative intervention to fundoplication for the treatment of gastroesophageal reflux disease (GERD). The aim of this study was to evaluate clinical outcomes following MSA for GERD control in comparison with laparoscopic fundoplication. A systematic electronic search for articles was performed in Medline, Embase, Web of Science, and Cochrane Library for single-arm cohort studies or comparative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…The findings from this study showed that the clinical outcomes for MSA and LF were favorable in regards to effectiveness, quality of life, satisfaction, PPI use, and safety, with low rates of complications and similar rates of clinic visits over 3 years. These results are in alignment with previously published effectiveness data for MSA and LF which showed that MSA and LF both lead to a decrease in HRQL score and an increase in patient satisfaction when compared with patient's preoperative symptoms [ 33 , 34 ]. The proportion of patients with the ability to belch with LF in our study increased over the first 2 years and then stayed relatively steady, possibly due to the loosening of the fundoplication over time (ie, transthoracic migration of the wrap) [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The findings from this study showed that the clinical outcomes for MSA and LF were favorable in regards to effectiveness, quality of life, satisfaction, PPI use, and safety, with low rates of complications and similar rates of clinic visits over 3 years. These results are in alignment with previously published effectiveness data for MSA and LF which showed that MSA and LF both lead to a decrease in HRQL score and an increase in patient satisfaction when compared with patient's preoperative symptoms [ 33 , 34 ]. The proportion of patients with the ability to belch with LF in our study increased over the first 2 years and then stayed relatively steady, possibly due to the loosening of the fundoplication over time (ie, transthoracic migration of the wrap) [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…In 2019, Guidozzi et al [56] conducted a systematic review and meta-analysis comparing MSA to laparoscopic fundoplication and concluded that the former achieves good GERD symptomatic control similar to that of fundoplication, with 3.3 % of patients requiring device removal. Our study is the first in literature to compare MSA and TIF2 based on similar patient reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most common side effect of LINX is dysphagia, whereas the most feared complications are device migration and esophageal erosion (~0.15%) ( 208 ). A systematic review comparing LINX to LARS reported a similar efficacy in controlling GERD symptoms and esophageal pH, with a larger reduction in gas bloating and improvement in belching in patients receiving the LINX procedure ( 209 ). Currently, the device is not licensed for use in severe erosive esophageal disease or large hiatal hernias ( 210 ).…”
Section: Endoscopic and Surgical Managementmentioning
confidence: 99%